Breakthroughs and new horizons in reproductive biology of rare and endangered animal species. Issue 3 (17th February 2019) - Comizzoli, Pierre; Holt, William V
Abstract: Because of higher extinction rates due to human and natural factors, more basic and applied research in reproductive biology is required to preserve wild species and design proper strategies leading to sustainable populations. The objective of the review is to highlight recent, inspiring breakthroughs in wildlife reproduction science that will set directions for future research and lead to more successes in conservation biology. Despite new tools and approaches allowing a better and faster understanding of key mechanisms, we still know little about reproduction in endangered species. Recently, the most striking advances have been obtained in nonmammalian species (fish, birds, amphibians, or corals) with the development of alternative solutions to preserve fertility or new information about parental nutritional influence on embryo development. A novel way has also been explored to consider the impact of environmental changes on reproduction—the allostatic load—in a vast array of species (from primates to fish). On the horizon, genomic tools are expected to considerably change the way we study wildlife reproduction and develop a concept of "precision conservation breeding." When basic studies in organismal physiology are conducted in parallel, new approaches using stem cells to create artificial gametes and gonads, innovations in germplasm storage, and more research on reproductive microbiomes will help to make a difference. Lastly, multiple challenges (for instance, poor integration of new tools in conservation programs, limited access to study animals, or few publication options) will have to be addressed if we want reproductive biology to positively impact conservation of biodiversity. Abstract : The optimization of new tools and approaches spanning from new biomarkers to bioinformatics will help to accelerate the exploration of wildlife reproduction and understand how it is impacted by environmental factors.